2014
DOI: 10.1530/eje-13-0966
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes in women with primary hyperparathyroidism

Abstract: Objective: To study pregnancy and pregnancy outcomes in women with primary hyperparathyroidism (PHPT) and in controls. Design: Register-based retrospective cohort study of women aged 16-44 years with a diagnosis of PHPT with age-and gender-matched non-exposed controls in Denmark. Methods: The patients and controls were identified using the Danish National Hospital Discharge Register for the period 1977-2010. The outcomes were determined using the Birth Register, the Abortion Register and the LPR (National Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 28 publications
3
58
2
Order By: Relevance
“…Only two studies to date have investigated the rate of pregnancy loss in women with gestational PHPT, and there were conflicting results (5,8). Norman et al (5) reported a 3.5-fold higher-than-normal rate of miscarriages among 77 pregnancies in 32 women with gestational PHPT from a single practice and suggested that surgical intervention in the second trimester might reduce the risk.…”
mentioning
confidence: 99%
“…Only two studies to date have investigated the rate of pregnancy loss in women with gestational PHPT, and there were conflicting results (5,8). Norman et al (5) reported a 3.5-fold higher-than-normal rate of miscarriages among 77 pregnancies in 32 women with gestational PHPT from a single practice and suggested that surgical intervention in the second trimester might reduce the risk.…”
mentioning
confidence: 99%
“…One study reported that primary hyperparathyroidism is associated with a 3-to 5-fold increased risk of miscarriage, primarily in the second trimester, and more likely in severe cases (serum calcium level >11.4 mg/dL) (4). Another study suggested that mildly affected patients do not have an increased risk of abortion (5). Up to 50% of neonates experience postpartum hypocalcemia secondary to elevated maternal calcium levels that suppress the fetal parathyroid glands (3).…”
Section: Discussionmentioning
confidence: 99%
“…Conservative medical therapy should be considered in the asymptomatic patient with a calcium level of <11 to 12 mg/dL (2,5). This includes a low-calcium diet and aggressive hydration, with or without a loop diuretic (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 PHPT is rare in pregnancy and is frequently associated, if unknown and untreated, with the risk of fetal complication and abortion: another register-based retrospective cohort study demonstrates how diagnosis of PHPT does not seem to increase the risk of abortion neither birth weight, length or Apgar score. 24 Neonatal primary hyperparathyroidism and familial hypocalciuric hypercalcemia are rare conditions caused by a defect in the gene coding for the calcium sensing receptor. In the first case newborns presented with hypotonia, poor feeding, constipation and respiratory distress: it is usually due to a homozygous mutation of calcium sensing receptor gene.…”
Section: Epidemiology and Etiologymentioning
confidence: 99%